2010
DOI: 10.3109/07853891003796752
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intensive glucose control on incidence of cardiovascular events in patients with type 2 diabetes: A meta-analysis

Abstract: An intensive glucose control strategy can effectively reduce the risk of major cardiovascular events but at the expense of a significantly increased risk of severe hypoglycemia in patients with type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 32 publications
2
20
0
1
Order By: Relevance
“…Although this result is seemingly contradicted by the UKPDS (3), where beneficial effects of intensive glycemic control emerged only after relatively lengthy follow-up of 10-20 years, at the end of the original UKPDS (20), intensive glycemic control showed a borderline preventive effect on MI. In addition, meta-analyses of randomized trials of intensive glycemic control have shown a preventive effect on MI after ;5 years of follow-up (21,22). The present results, in combination with previous findings, indicate that glycemic control is important to the prevention of MI and, more importantly, perhaps within a shorter time perspective than 10-20 years.…”
Section: Discussionsupporting
confidence: 76%
“…Although this result is seemingly contradicted by the UKPDS (3), where beneficial effects of intensive glycemic control emerged only after relatively lengthy follow-up of 10-20 years, at the end of the original UKPDS (20), intensive glycemic control showed a borderline preventive effect on MI. In addition, meta-analyses of randomized trials of intensive glycemic control have shown a preventive effect on MI after ;5 years of follow-up (21,22). The present results, in combination with previous findings, indicate that glycemic control is important to the prevention of MI and, more importantly, perhaps within a shorter time perspective than 10-20 years.…”
Section: Discussionsupporting
confidence: 76%
“…All forms of diabetes are clinically defined by increased blood glucose concentration and there is a progressive relationship between hyperglycemia and CVD, with CV risk rising approximately 20% for every 1.5 mM increase in fasting glucose levels [29], and for every 1% elevation in HbA1c levels [30]. Both epidemiological and pathophysiological studies have shown that hyperglycemia is an independent risk factor for CVD [6,31,32]. Hyperglycemia is known to increase flux through the HBP leading to increased production of UDP-N-acetylglucosamine (UDP-GlcNAc) - an essential substrate for both N-linked and O-linked protein glycosylation [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…The debate has continued because of the early cessation of the Action to Control Cardiovascular Risk for Diabetes (ACCORD) trial [12], because there was an increased mortality in the treatment group that included patients who were trying to achieve low HbA1c levels. Since 2008, a number of metaanalyses have been conducted on these clinical studies to highlight further the conflicting results [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Provision of appropriate tables and graphics [18][19][20][21][22][23] See also other supplementary tables…”
mentioning
confidence: 99%